Supply chain optimization, management and integration : emerging applications - Wang, John. (New York : Business Science Reference, 2011)
"This book presents readers with a rich collection of ideas from researchers who are bridging the gap between the latest in information technology and supply chain management, including theoretical, analytical, empirical research, and case studies of effective applications in the field of SCM"--Provided by publisher.
Includes bibliographies references and Index.
Keywords: Business logistics